10c=2c-6c+7

Since c is on the right side of the equation, switch the sides so it is on the left side of the equation.

2c-6c+7=10c

Subtract 6c from 2c.

-4c+7=10c

Subtract 10c from both sides of the equation.

-4c+7-10c=0

Subtract 10c from -4c.

-14c+7=0

-14c+7=0

Subtract 7 from both sides of the equation.

-14c=-7

Divide each term in -14c=-7 by -14.

-14c-14=-7-14

Cancel the common factor of -14.

Cancel the common factor.

-14c-14=-7-14

Divide c by 1.

c=-7-14

c=-7-14

Cancel the common factor of -7 and -14.

Factor -7 out of -7.

c=-7(1)-14

Cancel the common factors.

Factor -7 out of -14.

c=-7⋅1-7⋅2

Cancel the common factor.

c=-7⋅1-7⋅2

Rewrite the expression.

c=12

c=12

c=12

c=12

The result can be shown in multiple forms.

Exact Form:

c=12

Decimal Form:

c=0.5

Solve for c 10c=2c-6c+7